Stigma Dan Penerimaan Masyarakat Terhadap Anak Berkonflik Dengan Hukum (ABH) di Kota Makassar - serlyana; Mario; Muhammad Aksha Wahda (Universitas Muhammadiyah Metro, 2025)
Children in Conflict with the Law (CICL) often face social challenges after going through legal proceedings, particularly in terms of being reaccepted by the community. This study aims to: (1) Understand the public's perception of acceptance towards Children in Conflict with the Law (CICL); and (2) Identify the forms of stigma directed at Children in Conflict with the Law (CICL). This research is a case study. The researcher used data collection techniques including observation, documentation, and interviews. Triangulation was used as a procedure to verify data validity. The study applied data collection, data reduction, data modeling, and drawing conclusions as the data analysis techniques. The research results show that: (1) Community acceptance generally reflects a positive attitude towards CICL through emotional support, material assistance, and the provision of opportunities for self-improvement. (2) Stigmatization against CICL is more dominant within the family environment compared to the general public. The forms of stigma include labeling by family members, such as calling the child